Automated Knowledge Provider System with Natural Language Query Processing. Issue 5 (2nd September 2016) - Mukherjee, Prasenjit; Chakraborty, Baisakhi
ABSTRACT: Knowledge management system (KMS) is an effective tool for knowledge extraction, utilization, and dissemination. When a client or user sends query to the KMS, it is expected to provide response to the query. This paper proposes an automated knowledge provider system (AKPS) that accepts a natural language request of a user in a query–response model where natural language query will be automatically converted to the conceptual form of database. This model is a grammatical rule-based automated model that can extract knowledge from knowledge database resident within the AKPS independently without any manual intervention. The model maps the natural language query into the physical data model, and sends response to the user from a well-organized and well-defined database.